Enterprise knowledge management model: a knowledge tower - ÖZTEMEL, ERCAN (SPRINGER LONDON LTD, 2012)
One of the most important aspects of knowledge management (KM) is to create a system that is capable of providing mechanisms and methodologies allowing the right knowledge to be at the right place and at the right person as well as at the right time within an enterprise. There have been several models developed for this purpose. The main objectives of these models are to organize the knowledge activities to increase competitive advantage and turn the market share into a continuous and permanent superiority through utilizing the intellectual capital of the enterprise for better products and services. When existing models are carefully analyzed, it can be clearly seen that every model addresses different aspects of KM. While some of these models have been intensifying on the use of technology and production of knowledge, the others rather focus on the utilization of knowledge itself. Although these models point out the importance of managerial participation, they are mainly designed to be facilitated at operational levels. It is now obviously seen that there is a need for a new model that will deal with KM at strategic, tactic, and operational levels in an integrated manner. In this study, an enterprise knowledge management model (EKMM) is developed to facilitate this. The model is also called the Knowledge Tower due to its dynamics and tower-like infrastructure. EKMM does not only deal with utilizing the knowledge but also create KM strategies, knowledge culture as well as respective leveraging activities. It provides an extensive assessment capability to make sure that the KM practices are carried out as effectively as possible. This surely helps identifying the lack of implementations and areas requiring improvements.
Keywords: Knowledge; Knowledge management; Enterprise knowledge management; Knowledge tower; CONSTRUCTION; SYSTEMS